Third party cookies: what kind of world is without them? - Juškaitė, Justė; Janušauskaitė, Milda Aušrinė (Vilnius University Open Series, 2021)
In the article “Third-party cookies: what kind of world is without them?” the decision to remove third-party cookies is being analysed. This objective is being pursued, firstly, because of the problems that have arisen as a result of the “cookies” lack of compliance with law norms. Firefox and Safari were the first ones to make these changes, followed by Google, the largest “giant” in the market. Knowing the benefits of third-party cookies, it has become clear that there will be a need to find alternatives to replace this technology. The following solutions were proposed: “Privacy Sandbox”, contextual targeting, Firefox implemented an enhanced security program “Firefox 69”, and Safari’s privacy feature “Intelligent Tracking Protection”.The article also describes the possible nature of the digital advertising market after the implementation of this change, which will determine the necessity for marketing and business companies to change the strategies in the development of their activities. The article also analyses the legal mechanisms and aspirations of the European Union institutions in the legislative process, which will help to ensure consumer rights in the field of data protection.
Keywords: none